2018
DOI: 10.1002/anie.201712081
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Copper Dual Catalysis for the Cross‐Coupling of Aryl(trialkyl)silanes with Aryl Bromides

Abstract: Whereas aryl(trialkyl)silanes are considered to be ideal organometallic reagents for cross-coupling reactions owing to their stability, low toxicity, solubility, and easy accessibility, they are generally inert under typical cross-coupling conditions. Disclosed herein is a palladium/copper catalytic system that enables the cross-coupling of trimethyl, triethyl, tert-butyldimethyl, and triisopropyl aryl silanes with aryl bromides. This process is applicable to the sequential C-H and C-Si bond arylation of thiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The bromide substituted arenes can be further transformed into various other functional groups by well-known cross-coupling reactions. 24 Therefore, 2-bromoacetanilide was employed to investigate the scope of benzhydrol and the results were listed in Scheme 3 . The results clearly show that the functional groups, such as Me, F, Cl, Br, CF 3 , and Ph were all fully tolerated in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The bromide substituted arenes can be further transformed into various other functional groups by well-known cross-coupling reactions. 24 Therefore, 2-bromoacetanilide was employed to investigate the scope of benzhydrol and the results were listed in Scheme 3 . The results clearly show that the functional groups, such as Me, F, Cl, Br, CF 3 , and Ph were all fully tolerated in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[60] Thes ame group subsequently reported ad ual Pd/Cu catalytic system which allowed the coupling of ar ange of silyl groups under milder conditions (Scheme 10, conditions B). [61] Thee fficiencyo ft hese couplings was demonstrated with al arge scope of heterocyclic substrates,aswell as challenging polyfluorocarbocyclic nucleophiles,but the pyridine scope was once again limited.…”
Section: -Pyridylsilanes (Si)mentioning
confidence: 99%
“…The Hiyama group showed that 2‐pyridyltriethylsilanes could also be employed in a copper‐catalysed cross‐coupling reaction with aryl halides (Scheme 10, conditions A) [60] . The same group subsequently reported a dual Pd/Cu catalytic system which allowed the coupling of a range of silyl groups under milder conditions (Scheme 10, conditions B) [61] . The efficiency of these couplings was demonstrated with a large scope of heterocyclic substrates, as well as challenging polyfluorocarbocyclic nucleophiles, but the pyridine scope was once again limited.…”
Section: Traditional Nucleophilesmentioning
confidence: 99%